A Review of Tafamidis for the Treatment of Transthyretin-Related Amyloidosis. Issue 2 (December 2015) - Waddington Cruz, Márcia; Benson, Merril
Abstract Transthyretin (TTR)-related amyloidosis (ATTR) is a devastating disease which affects a combination of organs including the heart and the peripheral nerves, and which has a fatal outcome if not treated within a average of 10 years. Tafamidis, or 2-(3, 5-dichloro-phenyl)-benzoxazole-6-carboxylic acid, selectively binds to TTR with negative cooperativity and kinetically stabilizes wild-type native TTR and mutant TTR; tafamidis therefore has the potential to halt the amyloidogenic cascade initiated by TTR tetramer dissociation, monomer misfolding, and aggregation. The first tafamidis trial, Fx-005, evaluated the effect of 18 months of tafamidis treatment (20 mg once daily) on disease progression, as well as assessing its safety in TTR-FAP Val30Met patients. The secondary objective of this trial was to study the pharmacodynamic stabilization of mutated TTR. Tafamidis proved effective in reducing the progress of neuropathy, and in maintaining the nutritional status and quality of life of stage 1 (able to walk without support) Val3OMet TTR-FAP patients. Furthermore, TTR stabilization was achieved in more than 90% of patients. An extension study, Fx-006, was conducted to determine the long-term safety and tolerability of tafamidis and to assess the efficacy of the drug on slowing disease progression. No significant safety or tolerability issues were noticed. Taken together, the results from both trials indicated that the beneficial effects of tafamidis were sustained over a 30-month period and that starting treatment early is desirable. Results are expected from an extended open-label study but data that have already been presented show that long-term use of tafamidis in Val30Met patients is associated with reduced progression in polyneuropathy. Tafamidis was initially approved for commercial use in Europe in 2011 and has since been approved for use in Japan, Mexico, and Argentina where it is used as a first-line treatment option for patients with early-stage TTR-FAP. Patients should be carefully followed at referral centers to ascertain the individual response to treatment. In cases of discontinuation, liver transplantation and enrollment in clinical trials of novel drugs aimed mostly toward suppression of TTR production are options.